The effect of elastic abdominal binder use on respiratory function on persons with high spinal cord injury at orthostatic position. - Costa, Viviane de Souza Pinho; Costa, Bianca Teixeira; Jr, Rubens Alexandre da Silva; Filho, Ruy Moreira da Costa; Cardoso, Jefferson Rosa (Manual Therapy, Posturology & Rehabilitation Journal, 2015)
Introduction: Spinal cord injury causes respiratory muscles paralysis, especially in high thoracic paraplegia and tetraplegia with injury above or right on the sixth thoracic segment, and also biomechanics, volumes, capacities and respiratory pressures changes in affected people. The elastic abdominal binder provides a mechanical support for respiratory function treatment, assisting with abdominal restraint and abdominal compliance reduction while at orthostatic position. Objective: To verify the elastic abdominal binder effect on the respiratory function of people with spinal cord injuries during standing position with the help of orthostatic table, from vertical angle position of 60° and 90°. Method: The study included 56 people suffering from spinal cord injury with motor level above or right on the sixth thoracic segment. They were randomly divided into four distinct groups regarding the use or not of the binder and different inclinations of the orthostatic table during the evaluation procedure. The measured outcomes were vital capacity, tidal volume, inspiratory and expiratory pressure and oxygen saturation. The descriptive analysis presented according to average and standard deviation or median and interquartile. For the outcomes analysis of the five evaluations, the Analysis of Variance (ANOVA) of two factors with repeated measures was used. Statistical significance was set at 5%. Results: The values obtained from respiratory parameters showed no statistical significance regarding the elastic abdominal binder intervention nor on the angle of the standing position. Conclusion: There was no contrasting effect regarding the use of the binder among the evaluated people, therefore it should not be nominated as a standard procedure in the treatment of spinal cord injury at orthostatic position. However, this procedure should not be absolute contraindicated, thus its effect has not demonstrated any harm to participants.